Design and Experimental Verification of a 1/20 Scale Model of Quayside Container Crane Using Distortion Theory. (20th August 2019) - Li, Zhe; Ye, Fangping; Wu, Shiying
Abstract : The scale model is an effective method to research the performance of quayside container crane (QCC) under the seismic condition, but the model distortion usually exists in the similar design process which leads to the incomplete similarity between the scale model and prototype. In this investigation, the distortion theory and the prediction coefficient correction method are used to upgrade the quality of 1/20 QCC scale model and, then, the seismic response of the QCC prototype is obtained from the shake table scale model test. In the first step, the similarity ratio of the 1/20 QCC scale model is calculated by the similitude law and the size of scale model is obtained from the similarity constants. In the second step, the bending stiffness is selected and determined as the distortion term and, then, the relationship between the distortion coefficient and the prediction coefficient is obtained by the finite element prediction coefficient method. Furthermore, the three different scale models are manufactured and tested in the shake table experiment under different seismic conditions. It is found that the experimental test results are consistent with the numerical simulation results of the QCC prototype. It can be concluded that the QCC scale model can be used to predict the performance of the prototype under the different seismic conditions after corrected by distortion theory, and the distortion theory is an effective method to solve the incomplete similarity between the scale model and prototype.